New Waves in Aesthetics
XIX, 269 p.
Keywords: Leading young scholars present a collection of wide-ranging essays covering central problems in meta-aesthetics and aesthetic issues in the philosophy of mind, as well as offering analyses of key aesthetic concepts, new perspectives on the history of aesthetics, and specialized treatment of individual art forms.